A connective tissue disorder may underlie ESSENCE problems in childhood. (January 2017) - Baeza-Velasco, Carolina; Grahame, Rodney; Bravo, Jaime F.
Abstract: Background: Ehlers-Danlos syndrome hypermobility type, also known as Joint Hypermobility Syndrome (EDS-HT/JHS), is the most common hereditary disorder of the connective tissue (HDCT). It is characterized by tissue fragility, joint hypermobility and a wide range of articular and non-articular manifestations, which often appear in infancy. The clinical picture of EDS-HT/JHS is poorly known by the medical community, as is the presence of "ESSENCE" (Early Symptomatic Syndromes Eliciting Neurodevelopmental Clinical Examinations) problems in affected children. Aim: The present work reviews the clinical and empirical evidence for ESSENCE difficulties in children with EDS-HT/JHS. Method: A narrative review of the literature was undertaken following a comprehensive search of scientific online databases and reference lists. This included publications of quantitative and qualitative research. Results: Motor abnormality, hyperactivity/hypoactivity, inattention, speech/language, social interaction, behavioral, sleep, feeding and emotional problems are ESSENCE difficulties for which there is some evidence of an association with EDS-HT/JHS. Conclusion: Children with EDS-HT/JHS present ESSENCE problems that often coexist and tend to be recognized before the HDCT. Clinicians encountering children with ESSENCE problems should consider the possibility of an underlying HDCT such as EDS-HT/JHS, probably influencing neurodevelopmental attributes in a subgroup of children. Awareness of these interconnected clinical problems might help improve early referral, diagnosis and treatment of EDS-HT/JHS.